2021
DOI: 10.1007/s40519-021-01300-7
|View full text |Cite
|
Sign up to set email alerts
|

Everyday flexibility and functional milestones in anorexia nervosa: survey results from a mixed community sample

Abstract: Purpose This study examined the relationship between self-reported cognitive-behavioral flexibility scores on the Eating Disorder Flexibility Index (EDFLIX) and objective social and occupational functional milestones in participants with a lifetime diagnosis of anorexia nervosa (AN). The Work and Social Adjustment Scale (WSAS) was included to compare objective and subjective measures. Methods 114 female adult participants with a current (53.5%) or past (46.5%) full or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The results of the exploratory analysis suggest more systematic investigation of the associations between stress, clinical symptoms, and flexibility in AN is warranted. Lower self-reported flexibility was strongly associated with higher EDE-Q scores, and moderately associated with stress, consistent with past research in AN [ 6 , 7 ]. Higher stress was also a significant independent predictor of higher EDE-Q scores.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the exploratory analysis suggest more systematic investigation of the associations between stress, clinical symptoms, and flexibility in AN is warranted. Lower self-reported flexibility was strongly associated with higher EDE-Q scores, and moderately associated with stress, consistent with past research in AN [ 6 , 7 ]. Higher stress was also a significant independent predictor of higher EDE-Q scores.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the studies that examined non‐ED specific impairment, Bohn et al (2008), which used the CIA, reported no significant differences between AN and atypAN. Dann et al (2022a, 2022b) also reported no significant differences as measured with the Work and Social Adjustment Scale (WSAS). In contrast, Birgegard et al (2012) and Pauls et al (2022) found higher levels of impairment in the AN group than in the atypAN group with the CIA and Eating Disorders Quality of Life Scale (EDQLS), respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Nine (45%) studies examined the difference between AN and atypAN using the composite global score on the EDE or EDE‐Q. Five (56%) studies reported no significant differences between the two groups on global severity (Birgegard et al, 2012; Dann et al, 2022a, 2022b; Kim et al, 2023; Matthews et al, 2022; Rosello, Gledhill, Yi, Watkins, Harvey, Hosking, Viner et al, 2021; Rosello, Gledhill, Yi, Watkins, Harvey, Hosking, & Nicholls, 2021). Three (33%) studies reported the atypAN group had greater severity on the global composite score than the AN group (Garber et al, 2019; Jablonski et al, 2022; Sawyer et al, 2016), whereas one (11%) study reported the AN group had greater severity than the atypAN group (Wade & O'Shea, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, an additional axis devoted to functional outcomes is warranted. Improvements in everyday functioning are meaningful treatment outcomes for patients [ 72 ], and despite current illness, AN patients have enduring functional strengths which could be integrated into treatment [ 73 ]. What is so remarkable about AN is the oft-observed degree of resilience when it comes to academic achievement, or the ability to outperform others in a scholastic or work environment.…”
mentioning
confidence: 99%